Comparison of the Vacuum Mattress versus the Spine Board Alone for Immobilization of the Cervical Spine Injured Patient: A Biomechanical Cadaveric Study. Issue 24 (15th December 2017) - Prasarn, Mark L.; Hyldmo, Per Kristian; Zdziarski, Laura A.; Loewy, Evan; Dubose, Dewayne; Horodyski, MaryBeth; Rechtine, Glenn R.
Abstract : Study Design: A biomechanical cadaveric study. Objective: We sought to determine the amount of motion generated in an unstable cervical spine fracture with use of the vacuum mattress versus the spine board alone. Our hypothesis is that the vacuum mattress will better immobilize an unstable cervical fracture. Summary of Background Data: Trauma patients in the United States are immobilized on a rigid spine board, whereas in many other places, vacuum mattresses are used with the proposed advantages of improved comfort and better immobilization of the spine. Methods: Unstable subaxial cervical injuries were surgically created in five fresh whole human cadavers. The amount of motion at the injured motion segment during testing was measured using a Fastrak, three-dimensional, electromagnetic motion analysis device (Polhemus Inc.). The measurements recorded in this investigation included maximum displacements during application and removal of the device, while tilting to 90°, during a bed transfer, and a lift onto a gurney. Linear and angular displacements were compared using the Generalized Linear Model analysis of variance for repeated measures for each of the six dependent variables (three planes of angulations and three axes of displacement). Results: There was more motion in all six planes of motion during the application process with use of the spine board alone, and this was statistically significant for axial rotation ( P = 0.011), axial distraction ( P = 0.035), medial-lateral translation ( P = 0.027), and anteroposterior translation ( P = 0.026). During tilting, there was more motion with just the spine board, but this was only statistically significant for anteroposterior translation ( P = 0.033). With lifting onto the gurney, there was more motion with the spine board in all planes with statistical significance, except lateral bending. During the removal process, there was more motion with the spine board alone, and this was statistically significant for axial rotation ( P = 0.035), lateral bending ( P = 0.044), and axial distraction ( P = 0.023). Conclusion: There was more motion when using a spine board alone during typical maneuvers performed during early management of the spine injured patient than the vacuum mattress. There may be benefit of use of the vacuum mattress versus the spine board alone in preventing motion at an unstable, subaxial cervical spine injury. Level of Evidence: 2